Respuesta :

Answer:

The inverse of the function is  [tex]f^{-1}(x) =\sqrt[5]{\frac{x-7}{3}}[/tex]

Step-by-step explanation:

The steps to get the inverse of a function are:

  1. Replace f(x) with y
  2. Replace every x by y and every y by x
  3. Solve the new equation from for y
  4. Replace y with [tex]f^{-1}(x)[/tex]

∵ [tex]f(x)=3x^{5}+7[/tex]

- Replace f(x) by y

∴ [tex]y=3x^{5}+7[/tex]

- Replace every x by y and every y by x

∴  [tex]x=3y^{5}+7[/tex]

- Subtract 7 from both sides

∴ [tex]x-7=3y^{5}[/tex]

- Divide both sides by 3

∴ [tex]\frac{x-7}{3}=y^{5}[/tex]

- Insert fifth root for both sides

∴ [tex]\sqrt[5]{\frac{x-7}{3}}=y[/tex]

- Switch the two sides

∴ [tex]y=\sqrt[5]{\frac{x-7}{3}}[/tex]

- replace y by [tex]f^{-1}(x)[/tex]

∴ [tex]f^{-1}(x) =\sqrt[5]{\frac{x-7}{3}}[/tex]

The inverse of the function is  [tex]f^{-1}(x) =\sqrt[5]{\frac{x-7}{3}}[/tex]